Efficacy of haloxifop-r-methyl with different coadyuvants. (FAVE Sección Ciencias Agrarias, 2019)
In Argentina, thirteen biotypes of glyphosate-resistant weeds have been confi rmed, eight of these are grasses. To control grassy weeds herbicides such as haloxifop-R-methyl with the addition of mineral oil is recommended. Other additives to replace the mineral oil are currently offered in the market with equal or greater effi cacy and lower costs. The aim of this work was to evaluate the efficacy of haloxifop-R-methyl with different adjuvants (mineral oils, ethoxylated nonylphenol, methyl esters of vegetable oil, ethoxylated linear alcohol and oxo polyoxyethylenated alcohol), applied in oats 40 days after sowing. Effi cacy was determined by senescence and dry weight of the plants. The best herbicide action of haloxifop-R-methyl was with the use of mineral oil as an additive.
Keywords: additives; weeds; graminicides